Divergent migration strategies within a population of Snow Buntings - Samuelle Simard-Provençal; Oliver P. Love; Rebecca J. Jardine; Alysha Riquier; Patricia Rokitnicki; Sara Pearce Meijerink; François Vézina; Christina A. D. Semeniuk; Emily A. McKinnon (Journal of Ornithology, 2026)

A Meta‐Regression of 18 Wildfire Chronosequences Reveals Key Environmental Drivers and Knowledge Gaps in the Boreal Nitrogen Balance - Stefan F. Hupperts; Frank Berninger; Han Y. H. Chen; Nicole Fenton; Mélanie Jean; Kajar Köster; Markku Larjavaara; Michelle C. Mack; Marie‐Charlotte Nilsson; Marjo Palviainen; Anatoly Prokushkin; Jukka Pumpanen; et al. (Global Change Biology, 2025)
Climate change has increased the size and frequency of wildfires across the boreal biome. Severe wildfires in boreal forests have been found to trigger shifts from evergreen to deciduous canopies, which has cascading effects on carbon and nitrogen cycling. Ecosystem productivity and carbon uptake in boreal forests are strongly linked with nitrogen, and Earth system models increasingly depend on our understanding of the nitrogen balance to predict post‐fire carbon uptake. To investigate the post‐fire boreal nitrogen balance, we combined a mass balance approach and literature synthesis to estimate rates of nitrogen accumulation and nitrogen inputs across a network of 18 boreal wildfire chronosequences that varied in both wildfire regime and post‐fire canopy type, comprising 527 forest stands. We found that deciduous‐ or mixed‐dominance boreal forests establishing after severe, stand‐replacing fires had the highest nitrogen accumulation rates (15.7 ± 3.8 kg ha −1 year −1 ), while evergreen‐dominated forests establishing after surface‐ or mixed‐severity fires had the lowest nitrogen accumulation rates (1.4 ± 1.1 kg ha −1 year −1 ). Annual known inputs from nitrogen deposition and biological nitrogen fixation combined, estimated from published data, largely failed to explain the rate of nitrogen accumulation, particularly in deciduous or mixed‐dominance forests establishing after stand‐replacing fires, suggesting that the origins of most nitrogen in these forest types remain poorly understood. As the frequency of severe wildfires increases across the boreal biome and shifts toward deciduous canopies become more common, our study reveals a large knowledge gap in the resulting nitrogen balance that needs to be resolved in order to improve predictions of forest carbon uptake.

Examining the status of mangrove forest dynamics and community-led management on the Colombian Pacific coast - Paulo J. Murillo-Sandoval; Mauricio Perea-Ardila; Marc Simard (Ocean & Coastal Management, 2025)

Discharge of ballast residual sediments during de-ballasting procedures: A more realistic estimate of propagule pressure - Nathalie Simard; Andrea M. Weise; André Rochon; Elizabeta Briski; Hugh J. MacIsaac; Christopher W. McKindsey (Marine Pollution Bulletin, 2024)

A regional map of mangrove extent for Myanmar, Thailand, and Cambodia shows losses of 44% by 1996 - Priscilla Baltezar; Paulo J. Murillo-Sandoval; Kyle C. Cavanaugh; Cheryl Doughty; David Lagomasino; Thida Tieng; Marc Simard; Temilola Fatoyinbo (Frontiers in Marine Science, 2023)
Southeast Asia is home to some of the planet’s most carbon-dense and biodiverse mangrove ecosystems. There is still much uncertainty with regards to the timing and magnitude of changes in mangrove cover over the past 50 years. While there are several regional to global maps of mangrove extent in Southeast Asia over the past two decades, data prior to the mid-1990s is limited due to the scarcity of Earth Observation (EO) data of sufficient quality and the historical limitations to publicly available EO. Due to this literature gap and research demand in Southeast Asia, we conducted a classification of mangrove extent using Landsat 1-2 MSS Tier 2 data from 1972 to 1977 for three Southeast Asian countries: Myanmar, Thailand, and Cambodia. Mangrove extent land cover maps were generated using a Random Forest machine learning algorithm that effectively mapped a total of 15,420.51 km 2 . Accuracy assessments indicated that the classification for the mangrove and non-mangrove class had a producer’s accuracy of 80% and 98% user’s accuracy of 90% and 96%, and an overall accuracy of 95%. We found a decline of 6,830 km 2 between the 1970s and 2020, showing that 44% of the mangrove area in these countries has been lost in the past 48 years. Most of this loss occurred between the 1970s and 1996; rates of deforestation declined dramatically after 1996. This study also elaborated on the nature of mangrove change within the context of the social and political ecology of each case study country. We urge the remote sensing community to empathetically consider the local need of those who depend on mangrove resources when discussing mangrove loss drivers.

Mangroves Cover Change Trajectories 1984-2020: The Gradual Decrease of Mangroves in Colombia - Paulo J. Murillo-Sandoval; Lola Fatoyinbo; Marc Simard (Frontiers in Marine Science, 2022)
Awareness of the significant benefits of mangroves to human lives and their role in regulating environmental processes has increased during the recent decades. Yet there remains significant uncertainty about the mangrove change trajectories and the drivers of change at national scales. In Colombia, the absence of historical satellite imagery and persistent cloud cover have impeded the accurate mapping of mangrove extent and change over time. We create a temporally consistent Landsat-derived dataset using the LandTrendr algorithm to track the historical land cover and mangrove conversion from 1984-2020 across Colombia. Over this period, mangrove extent decreased by ~48.000ha (14% of total mangrove area). We find a gradual reduction of mangrove extent along the Pacific coast since 2004, whereas, in the Caribbean, mangrove cover declined around during 1984-1988 and also after 2012. Our time-series analysis matches with drivers of mangrove change at three local sites. For instance, hydroclimatic events, dredging activities, and high sediment loads transported by the rivers have collectively improved mangrove recovery in some sites. In contrast, human activities pressure linked to agricultural expansion and road construction have degraded mangroves. The transition from dense mangrove to other vegetation types is the most significant conversion affecting mangrove cover in Colombia, impacting an area of 38,469 ± 2,829 ha. We anticipate increased mangrove loss, especially along the Pacific coast, resulting from intensified human activity. Prioritization of conservation areas is needed to support local institutions, maintain currently protected areas, and develop strategies (e.g. payment for ecosystem services) to preserve one of the most pristine mangrove regions in the Western Hemisphere.

Water resource development and sturgeon (Acipenseridae): state of the science and research gaps related to fish passage, entrainment, impingement and behavioural guidance - S. J. Cooke; J. J. Cech; D. M. Glassman; J. Simard; S. Louttit; R. J. Lennox; L. Cruz-Font; C. M. O’Connor (Reviews in Fish Biology and Fisheries, 2020)

The effects of ectomycorrhizal fungal networks on seedling establishment are contingent on species and severity of overstorey mortality - Gregory J. Pec; Suzanne W. Simard; James F. Cahill; Justine Karst (Mycorrhiza, 2020)

Survey of primary care physicians’ views about breast and ovarian cancer screening for true BRCA1/2 non-carriers - S. Pelletier; G. Larouche; J. Chiquette; Z. El Haffaf; W. D. Foulkes; P. Hamet; J. Simard; M. Dorval (Journal of Community Genetics, 2020)

Assessment of recreational boating as a vector for marine non-indigenous species on the Atlantic coast of Canada - M. Pelletier-Rousseau; R. Bernier; C. Clarke Murray; D. Drolet; A. Lacoursière-Roussel; A. Locke; J. L. Martin; C. H. McKenzie; C. W. McKindsey; T. W. Therriault; N. Simard (Biological Invasions, 2019)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Decline of ectomycorrhizal fungi following a mountain pine beetle epidemic - Roland Treu; Justine Karst; Morgan Randall; Gregory J. Pec; Paul W. Cigan; Suzanne W. Simard; Janice E. K. Cooke; Nadir Erbilgin; James F. Cahill (Ecology, 2014)
Forest die‐off caused by mountain pine beetle (MPB; Dendroctonus ponderosa ) is rapidly transforming western North American landscapes. The rapid and widespread death of lodgepole pine ( Pinus contorta ) will likely have cascading effects on biodiversity. One group particularly prone to such declines associated with MPB are ectomycorrhizal fungi, symbiotic organisms that can depend on pine for their survival, and are critical for stand regeneration. We evaluated the indirect effects of MPB on above‐ (community composition of epigeous sporocarps) and belowground (hyphal abundance) occurrences of ectomycorrhizal fungi across 11 forest stands. Along a gradient of mortality (0–82% pine killed), macromycete community composition changed; this shift was driven by a decrease in the species richness of ectomycorrhizal fungi. Both the proportion of species that were ectomycorrhizal and hyphal length in the soil declined with increased MPB‐caused pine mortality; 70% in stands without MPB attacks. The rapid range expansion of a native insect results not only in the widespread mortality of an ecologically and economically important pine species, but the effect of MPB may also be exacerbated by the concomitant decline of fungi crucial for recovery of these forests.

Disruption of Ion Homeostasis in the Neurogliovascular Unit Underlies the Pathogenesis of Ischemic Cerebral Edema - Arjun Khanna; Kristopher T. Kahle; Brian P. Walcott; Volodymyr Gerzanich; J. Marc Simard (Translational Stroke Research, 2014)

Taxon‐ and vector‐specific variation in species richness and abundance during the transport stage of biological invasions - Elizabeta Briski; Sarah A. Bailey; Oscar Casas-Monroy; Claudio DiBacco; Irena Kaczmarska; Janice E. Lawrence; Jonas Leichsenring; Colin Levings; Michael L. MacGillivary; Christopher W. McKindsey; Leslie E. Nasmith; Marie Parenteau; et al. (Limnology and Oceanography, 2013)
Recent empirical and statistical evidence suggest that propagule pressure (i.e., number of individuals introduced per event, and the number and frequency of events) and colonization pressure (i.e., number of species released per event, and the number and frequency of events) are of vital importance to invasion success. To explore possible changes in propagule and colonization pressure during the transport stage of the invasion process, we examine abundance and species richness of virus‐like particles, bacteria, diatoms, dinoflagellates, and invertebrates transported in commercial ships—a leading vector for global spread of aquatic nonindigenous species. We collected 154 ballast water samples from ships that had performed or were exempt from ballast water exchange (BWE) prior to arrival at Pacific and Atlantic ports in Canada and Laurentian Great Lakes ports. We found that abundance and species richness varied across taxa and regions, with ships arriving to the Atlantic region carrying the highest abundance of taxa. The highest species richness of invertebrates and diatoms was recorded from ships arriving to the Pacific, whereas the richest communities of dinoflagellates occurred in the Atlantic region. We also found that BWE had no effect on abundance or species richness of most taxa (dinoflagellates, diatoms, bacteria, and virus‐like particles), whereas the effect on abundance of invertebrates was not clear. Finally, longer voyages resulted in lower abundance of all taxa except dinoflagellates, and lower species richness of diatoms. Paradoxically, the elevated abundance and species richness of dinoflagellates following BWE suggest that this group could have enhanced invasion potential when ships manage ballast water by exchange.

Transient receptor potential melastatin 4 and cell death - J. Marc Simard; S. Kyoon Woo; Volodymyr Gerzanich (Pflügers Archiv - European Journal of Physiology, 2012)

miR-20a represses endothelial cell migration by targeting MKK3 and inhibiting p38 MAP kinase activation in response to VEGF - Anne-Laure Pin; François Houle; Maëva Guillonneau; Éric R. Paquet; Martin J. Simard; Jacques Huot (Angiogenesis, 2012)

Vertical partitioning between sister species of R hizopogon fungi on mesic and xeric sites in an interior D ouglas‐fir forest - Kevin J. Beiler; Suzanne W. Simard; Valerie LeMay; Daniel M. Durall (Molecular Ecology, 2012)
Understanding ectomycorrhizal fungal ( EMF ) community structure is limited by a lack of taxonomic resolution and autecological information. R hizopogon vesiculosus and R hizopogon vinicolor ( B asidiomycota) are morphologically and genetically related species. They are dominant members of interior D ouglas‐fir ( P seudotsuga menziesii var . glauca ) EMF communities, but mechanisms leading to their coexistence are unknown. We investigated the microsite associations and foraging strategy of individual R . vesiculosus and R . vinicolor genets. Mycelia spatial patterns, pervasiveness and root colonization patterns of fungal genets were compared between R hizopogon species and between xeric and mesic soil moisture regimes. R hizopogon spp. mycelia were systematically excavated from the soil and identified using microsatellite DNA markers. R hizopogon vesiculosus mycelia occurred at greater depth, were more spatially pervasive, and colonized more tree roots than R . vinicolor mycelia. Both species were frequently encountered in organic layers and between the interface of organic and mineral horizons. They were particularly abundant within microsites associated with soil moisture retention. The occurrence of R . vesiculosus shifted in the presence of R . vinicolor towards mineral soil horizons, where R . vinicolor was mostly absent. This suggests that competition and foraging strategy may contribute towards the vertical partitioning observed between these species. R hizopogon vesiculosus and R . vinicolor mycelia systems occurred at greater mean depths and were more pervasive in mesic plots compared with xeric plots. The spatial continuity and number of trees colonized by genets of each species did not significantly differ between soil moisture regimes.

Heparin Reduces Neuroinflammation and Transsynaptic Neuronal Apoptosis in a Model of Subarachnoid Hemorrhage - J. Marc Simard; Cigdem Tosun; Svetlana Ivanova; David B. Kurland; Caron Hong; Leanne Radecki; Carter Gisriel; Rupal Mehta; David Schreibman; Volodymyr Gerzanich (Translational Stroke Research, 2012)

Glibenclamide—10-h Treatment Window in a Clinically Relevant Model of Stroke - J. Marc Simard; Seung Kyoon Woo; Natalia Tsymbalyuk; Oksana Voloshyn; Vladimir Yurovsky; Svetlana Ivanova; Ryan Lee; Volodymyr Gerzanich (Translational Stroke Research, 2012)

Targeting the Microvasculature in Cerebral Ischemia—Go (or Stop Going) with the Flow - J. Marc Simard; Volodymyr Gerzanich (Translational Stroke Research, 2011)

Inflammation of the Choroid Plexus and Ependymal Layer of the Ventricle Following Intraventricular Hemorrhage - Philippe F. Simard; Cigdem Tosun; Ludmila Melnichenko; Svetlana Ivanova; Volodymyr Gerzanich; J. Marc Simard (Translational Stroke Research, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Genetic association of physically unlinked islands of genomic divergence in incipient species of Anopheles gambiae - BRADLEY J. WHITE; CHANGDE CHENG; FREDERIC SIMARD; CARLO COSTANTINI; NORA J. BESANSKY (Molecular Ecology, 2010)
Previous efforts to uncover the genetic underpinnings of ongoing ecological speciation of the M and S forms of the African malaria vector Anopheles gambiae revealed two centromere‐proximal islands of genetic divergence on X and chromosome 2. Under the assumption of considerable ongoing gene flow between M and S, these persistently divergent genomic islands were widely considered to be ‘speciation islands’. In the course of microarray‐based divergence mapping, we discovered a third centromere‐associated island of divergence on chromosome 3, which was validated by targeted re‐sequencing. To test for genetic association between the divergence islands on all three chromosomes, SNP‐based assays were applied in four natural populations of M and S spanning West, Central and East Africa. Genotyping of 517 female M and S mosquitoes revealed nearly complete linkage disequilibrium between the centromeres of the three independently assorting chromosomes. These results suggest that despite the potential for inter‐form gene flow through hybridization, actual (realized) gene flow between M and S may be substantially less than commonly assumed and may not explain most shared variation. Moreover, the possibility of very low gene flow calls into question whether diverged pericentromeric regions—characterized by reduced levels of variation and recombination—are in fact instrumental rather than merely incidental to the speciation process.

Species patterns in foliar nitrogen concentration, nitrogen content and 13C abundance for understory saplings across light gradients - J. M. Kranabetter; S. W. Simard; R. D. Guy; K. D. Coates (Plant and Soil, 2010)

Minimum pulses of stable and radioactive carbon isotopes to detect belowground carbon transfer between plants - Leanne J. Philip; Suzanne W. Simard (Plant and Soil, 2008)

Differential gene expression in incipient species of Anopheles gambiae - BRYAN J. CASSONE; KARINE MOULINE; MATTHEW W. HAHN; BRADLEY J. WHITE; MARCO POMBI; FREDERIC SIMARD; CARLO COSTANTINI; NORA J. BESANSKY (Molecular Ecology, 2008)
A speciation process is ongoing in the primary vector of malaria in Africa, Anopheles gambiae . Assortatively mating incipient species known as the M and S forms differentially exploit larval breeding sites associated with different ecological settings. However, some ongoing gene flow between M and S limits significant genomic differentiation mainly to small centromere‐proximal regions on chromosomes X and 2L, termed ‘speciation islands’ with the expectation that they contain the genes responsible for reproductive isolation. As the speciation islands exhibit reduced recombination and low polymorphism, more detailed genetic analysis using fine‐scale mapping is impractical. We measured global gene expression differences between M and S using oligonucleotide microarrays, with the goal of identifying candidate genes that could be involved in this ongoing speciation process. Gene expression profiles were examined in two independent colonies of both forms at each of three developmental periods of interest: fourth instar larvae, virgin females, and gravid females. Patterns were validated on a subset of genes using quantitative real‐time reverse transcription polymerase chain reaction of RNA samples from laboratory colonies and wild mosquitoes collected from Cameroon and Burkina Faso. Considered across all three developmental periods, differentially expressed genes represented ~1–2% of all expressed genes. Although disproportionately represented in the X speciation island, the vast majority of genes were located outside any speciation island. Compared to samples from the other developmental periods, virgin females were characterized by more than twice as many differentially expressed genes, most notably those implicated in olfaction and potentially, mate recognition.

Do escaped transgenes persist in nature? The case of an herbicide resistance transgene in a weedy Brassica rapa population - S. I. WARWICK; A. LÉGÈRE; M.‐J. SIMARD; T. JAMES (Molecular Ecology, 2008)
The existence of transgenic hybrids resulting from transgene escape from genetically modified (GM) crops to wild or weedy relatives is well documented but the fate of the transgene over time in recipient wild species populations is still relatively unknown. This is the first report of the persistence and apparent introgression, i.e. stable incorporation of genes from one differentiated gene pool into another, of an herbicide resistance transgene from Brassica napus into the gene pool of its weedy relative, Brassica rapa , monitored under natural commercial field conditions. Hybridization between glyphosate‐resistant [herbicide resistance (HR)] B. napus and B. rapa was first observed at two Québec sites, Ste Agathe and St Henri, in 2001. B. rapa populations at these two locations were monitored in 2002, 2003 and 2005 for the presence of hybrids and transgene persistence. Hybrid numbers decreased over the 3‐year period, from 85 out of ~200 plants surveyed in 2002 to only five out of 200 plants in 2005 (St Henri site). Most hybrids had the HR trait, reduced male fertility, intermediate genome structure, and presence of both species‐specific amplified fragment length polymorphism markers. Both F 1 and backcross hybrid generations were detected. One introgressed individual, i.e. with the HR trait and diploid ploidy level of B. rapa, was observed in 2005. The latter had reduced pollen viability but produced ~480 seeds. Forty‐eight of the 50 progeny grown from this plant were diploid with high pollen viability and 22 had the transgene (1:1 segregation). These observations confirm the persistence of the HR trait over time. Persistence occurred over a 6‐year period, in the absence of herbicide selection pressure (with the exception of possible exposure to glyphosate in 2002), and in spite of the fitness cost associated with hybridization.

Pyrethroid tolerance is associated with elevated expression of antioxidants and agricultural practice in Anopheles arabiensis sampled from an area of cotton fields in Northern Cameroon - PIE MÜLLER; MOUHAMADOU CHOUAÏBOU; PATRICIA PIGNATELLI; JOSIANE ETANG; EDWARD D. WALKER; MARTIN J. DONNELLY; FRÉDÉRIC SIMARD; HILARY RANSON (Molecular Ecology, 2008)
Spraying of agricultural crops with insecticides can select for resistance in nontarget insects and this may compromise the use of insecticides for the control of vector‐borne diseases. The tolerance of the malaria vector, Anopheles arabiensis to deltamethrin was determined in a field population from a cotton‐growing region of Northern Cameroon both prior to and midway through the 4‐month period of insecticide application to the cotton crop. A 1.6‐fold increase in the median knockdown time was observed. To determine whether this increased tolerance was associated with constitutively elevated levels of genes commonly associated with insecticide resistance, RNA was extracted from F 1 progeny from family lines of field‐caught mosquitoes and hybridized to the Anopheles gambiae detox chip. The experimental design avoided the confounding effects of colonization, and this study is the first to measure gene expression in the progeny of gravid, wild‐caught mosquitoes. Several genes with antioxidant roles, including superoxide dismutases, a glutathione S‐transferase and a thioredoxin‐dependent peroxidase, and a cytochrome P450 showed elevated expression in mosquito families collected during the insecticide‐spraying programme. These genes may constitute an important general defence mechanism against insecticides. Intriguingly, the levels of expression of these genes were strongly correlated suggesting a common regulatory mechanism.

Metallogeny of the Mont-de-l’Aigle IOCG deposit, Gaspé Peninsula, Québec, Canada - M. Simard; G. Beaudoin; J. Bernard; A. Hupé (Mineralium Deposita, 2006)

Hybridization between transgenic Brassica napus L. and its wild relatives: Brassica rapa L., Raphanus raphanistrum L., Sinapis arvensis L., and Erucastrum gallicum (Willd.) O.E. Schulz - S. I. Warwick; M.-J. Simard; A. Légère; H. J. Beckie; L. Braun; B. Zhu; P. Mason; G. Séguin-Swartz; C. N. Stewart (Theoretical and Applied Genetics, 2003)

PCNA Up-Regulation in Cerebral Vessels with Angiotensin II-Hypertension: Abnormal Regulation of Ca2+ Channel and Nitrate Tolerance Associated with Alternative Splicing of cGKI - A. Ivanov; S. Ivanova; L. V. Melnitchenko; V. Gerzanich; M. F. Shuba; J. M. Simard (Neurophysiology, 2003)

Complete nucleotide sequence, genomic organization, and promoter analysis of the murine survival motor neuron gene (Smn) - Christine J. DiDonato; Thierry Brun; Louise R. Simard (Mammalian Genome, 1999)

Effects of cement kiln dust on soil and potato crop quality - J. Lafond; R. R. Simard (American Journal of Potato Research, 1999)

Growing American ginseng in maple forests as an alternative land-use system in Québec, Canada - I. Nadeau; A. Olivier; R. R. Simard; J. Coulombe; S. Yelle (Agroforestry Systems, 1998)

Genetic Determinants of Pseudomonas aeruginosa Colonization in Cystic Fibrosis Patients in Canada - M. De Braekeleer; C. Allard; J.-P. Leblanc; G. Aubin; F. Simard (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Genetic determinants ofPseudomonas aeruginosa colonization in cystic fibrosis patients in Canada - M. Braekeleer; C. Allard; J. -P. Leblanc; G. Aubin; F. Simard (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Genetic and physical mapping of the mouse host resistance locus Lgn1 - Eduarto Diez; Marie-Claire Beckers; Eric Ernst; Christine J. DiDonato; Louise R. Simard; Celine Morissette; Francine Gervais; Shin-Ichi Yoshida; Philippe Gros (Mammalian Genome, 1997)

The mouse neuronal apoptosis inhibitory protein gene maps to a conserved syntenic region of mouse chromosome 13 - Christine J. DiDonato; Joseph H. Nadeau; Louise R. Simard (Mammalian Genome, 1997)

Synthetic peptides corresponding to the F protein of RSV stimulate murine B and T cells but fail to confer protection - M. Trudel; E. J. Stott; G. Taylor; D. Oth; G. Mercier; F. Nadon; C. Séguin; C. Simard; M. Lacroix (Archives of Virology, 1991)